2021
DOI: 10.3390/ijms222312642
|View full text |Cite
|
Sign up to set email alerts
|

CRB1-Related Retinal Dystrophies in a Cohort of 50 Patients: A Reappraisal in the Light of Specific Müller Cell and Photoreceptor CRB1 Isoforms

Abstract: Pathogenic variants in CRB1 lead to diverse recessive retinal disorders from severe Leber congenital amaurosis to isolated macular dystrophy. Until recently, no clear phenotype-genotype correlation and no appropriate mouse models existed. Herein, we reappraise the phenotype-genotype correlation of 50 patients with regards to the recently identified CRB1 isoforms: a canonical long isoform A localized in Müller cells (12 exons) and a short isoform B predominant in photoreceptors (7 exons). Twenty-eight patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…Recurrent variants are in bold. The location of the variants illustrates clustering in specific exons [Colour figure can be viewed at wileyonlinelibrary.com]bridge 5. This finding is compatible with the CRB2 variant data, as many of the missense variants in CRB2 involve cysteine residues.…”
supporting
confidence: 71%
“…Recurrent variants are in bold. The location of the variants illustrates clustering in specific exons [Colour figure can be viewed at wileyonlinelibrary.com]bridge 5. This finding is compatible with the CRB2 variant data, as many of the missense variants in CRB2 involve cysteine residues.…”
supporting
confidence: 71%
“…Both the p.Ile205Aspfs*13 and p.Ile167_Gly169del variants identified in the township of Ciales have previously been identified in France. 13 Meanwhile, the p.Ile167_Gly169del variant has been identified in Brazilian and Spanish cohorts. 14,15 A study based on a small European cohort of patients identified this variant in all their patients indicating further European influence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the positions of mutation may also affect distinct isoforms and lead to different phenotypes. Indeed, Mairot et al (30) reported that the phenotype in CRB1 patients might be dependent on the severity of Müller cell impairment related to isoform diversity. In addition, experiments based on gene knockout mouse models indicated a modifying role of CRB2 (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%